2019
DOI: 10.1007/s12687-019-00411-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with willingness to provide biospecimens for genetics research among African American cancer survivors

Abstract: This study evaluated factors associated with willingness to provide biospecimens for cancer genetic research among African American cancer survivors. A total of 200 African American adults diagnosed with breast, colon, and/or prostate cancers completed a self-administered survey. Family history information, beliefs about cancer research, cancer genetics and disparities knowledge, willingness to provide a biospecimen, and demographics were obtained. Chi-square, independent samples t tests, and logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…The importance of this theme cannot be overstated, as it has been identified as the overarching theme that allows the AARP to prioritize participation over their fears related to the justifiable distrust from centuries of mistreatment of AARPs by the research community. Altruistic motivational behaviors to participate are consistent with previous studies, as the motivation to research was either identified as altruism or AARPs' desires to help future generations 39–41. Moreover, this study supports that AARPs are willing to participate despite this history.…”
Section: Conclusion and Implications For Research And Practicesupporting
confidence: 87%
See 1 more Smart Citation
“…The importance of this theme cannot be overstated, as it has been identified as the overarching theme that allows the AARP to prioritize participation over their fears related to the justifiable distrust from centuries of mistreatment of AARPs by the research community. Altruistic motivational behaviors to participate are consistent with previous studies, as the motivation to research was either identified as altruism or AARPs' desires to help future generations 39–41. Moreover, this study supports that AARPs are willing to participate despite this history.…”
Section: Conclusion and Implications For Research And Practicesupporting
confidence: 87%
“…AARPs' desires to help future generations. [39][40][41] Moreover, this study supports that AARPs are willing to participate despite this history. Therefore, all nurses and research team members need to acknowledge, examine the history, and receive cultural sensitivity training before engaging with the AA community.…”
Section: Strengths and Limitationssupporting
confidence: 78%
“…Studies have found factors associated with increased acceptance and willingness, which includes risk perception and family experience 37 , 38 and good knowledge of genetics. 39 These factors, however, were not directly significant in deciding whether to have genetic test or not in this study. To encourage testing for the most at risk, women are currently advised to test for the BRCA1/2 gene mutation if a family member has tested positive for it, or if a close relative has been diagnosed with cancer.…”
Section: Discussionmentioning
confidence: 55%
“…Trust in provider, researcher, or institution Buy-in/endorsement of a trusted provider, 27,29,31,33 good reputation of institution 27,33 on the basis of a family members' or friends' previous experience with a researcher or physician 33 medical centers/clinics that have well-established and longstanding community engagement and outreach programs 27,33 Patient-provider communication Adequate time with a provider, 31 physician's positive rapport with the patient base 27,31,33 Moderators Characteristics positively associated with willingness to donate biospecimens or likelihood of research participation Lower stage of cancer (0/I v II/IV) compared with higher stages (not metastatic) 24,26,31 ; higher perceived well-being 26,31 ; financial security 20,28 ; being a male cancer survivor (compared with female) 28 ; patients undergoing active surveillance (v active treatment or no treatment) 24 having an established sense of trust in an institution, possibly on the basis of the clinical experiences of friends or family members. 33 One study demonstrated that the most robust predictor of patient participation in biospecimen or genetic research was satisfaction with the level of provider communication including the length of time patients spent discussing the benefits and risks of research participation with their oncologist.…”
Section: Lack Of Research Transparencymentioning
confidence: 99%
“…All 10 studies described barriers to engaging B/AA people with cancer in biospecimen research [24][25][26][27][28][29][30][31][32][33] and were related to lack of awareness, fear, mistrust, logistical concerns, and/or study characteristics (Table 2).…”
Section: Barriersmentioning
confidence: 99%